2018
DOI: 10.1016/j.biopsych.2018.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Air Pollution Exposure During Fetal Life, Brain Morphology, and Cognitive Function in School-Age Children

Abstract: Exposure to fine particles during fetal life was related to child brain structural alterations of the cerebral cortex, and these alterations partially mediated the association between exposure to fine particles during fetal life and impaired child inhibitory control. Such cognitive impairment at early ages could have significant long-term consequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
110
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 193 publications
(116 citation statements)
references
References 44 publications
4
110
0
2
Order By: Relevance
“…Another recent study with a large sample of schoolchildren with brain MRI showed a relationship between the residential exposure to air pollution during pregnancy and a decrease in pre-frontal white matter in areas related with attention. 32 Consistent with these findings, recent retrospective studies in children reported that specific time windows during gestation are crucial for several cognitive functions 33 and autism. 34 Hence, the windows of sensitivity to air pollution exposure in utero in human beings are yet to be defined, for each specific environment, profile of pollutants, and socio-economic and ethnic groups.…”
Section: Vulnerable?supporting
confidence: 56%
See 3 more Smart Citations
“…Another recent study with a large sample of schoolchildren with brain MRI showed a relationship between the residential exposure to air pollution during pregnancy and a decrease in pre-frontal white matter in areas related with attention. 32 Consistent with these findings, recent retrospective studies in children reported that specific time windows during gestation are crucial for several cognitive functions 33 and autism. 34 Hence, the windows of sensitivity to air pollution exposure in utero in human beings are yet to be defined, for each specific environment, profile of pollutants, and socio-economic and ethnic groups.…”
Section: Vulnerable?supporting
confidence: 56%
“…The same study showed no changes in brain structure related to air pollution exposure, possibly because of the window of exposure (in utero vs childhood exposure) in that study. Another recent study with a large sample of schoolchildren with brain MRI showed a relationship between the residential exposure to air pollution during pregnancy and a decrease in pre‐frontal white matter in areas related with attention . Consistent with these findings, recent retrospective studies in children reported that specific time windows during gestation are crucial for several cognitive functions and autism .…”
Section: Are Children More Vulnerable?mentioning
confidence: 55%
See 2 more Smart Citations
“…In utero exposure to numerous neurotoxicants results in lasting brain deficits in children, as also first shown for lead, methylmercury and ethanol. Pre‐natal exposure to air pollutants can result in white matter impairment, as seen in follow‐up studies of children, and school performance improved more slowly in children exposed to elevated levels of air pollution . Other organ systems, such as the cardiovascular, the respiratory, the reproductive and the immune systems, are also known to be affected by early‐life exposures.…”
Section: Vulnerable Developmentmentioning
confidence: 99%